A kind of organic silicon polymer and its preparation method, a kind of solvent-free polyorganosiloxane composite
By introducing branched silicone macromolecular polymers containing cyclic siloxanes, the problem of the aging release force of solvent-free polyorgano-siloxane composites increased under high temperature and high speed conditions is solved, and stable release is achieved and increased residual adhesion.
Patent Information
- Application Number
- CN202210048278.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-01-17
AI Technical Summary
The existing solvent-free polyorganosiloxane composites have increased aging release force under high temperature and high speed conditions, resulting in the problem of inability to tear the product.
A branched silicone macromolecular polymer containing cyclic siloxane is introduced to improve the reactive activity and curing speed of reactive functional groups, form a fully cured anti-adhesion coating, and reduce the amount of polyorganohydrogen siloxane.
The stability of the aging release force under room temperature storage conditions is achieved, which reduces the possibility of aging release force increases, improves the residual adhesion rate and release force, and reduces the amount of catalyst.
Smart Images

Figure BDA0003472655460000051 
Figure BDA0003472655460000061 
Figure BDA0003472655460000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and specifically relates to an organosilicon polymer and a preparation method and application thereof, which is particularly suitable for high-speed coating of release agent materials. Background Art
[0002] Organic silicon anti-adhesive coating refers to a substrate with an anti-adhesive film coated on the surface, which can easily peel off highly adhesive substances. The chemicals that play the role of anti-adhesion and isolation are called isolation agents. Organic silicon isolation agents are currently the most widely used isolation agents because of their low toxicity, surface tension of 20-24mN / m, good wettability with paper, easy to form a firm film on the surface of paper, wide temperature application range, and low migration to adhesives. Organic silicon is used as a paper anti-adhesive agent. The mechanism of action is that the methyl group can rotate freely on the surface of the substrate, so that it can be arranged in an orderly and dense manner on the surface of the substrate, which can effectively prevent the adhesive molecules or segments from penetrating into the substrate. The methyl group itself has very low polarity, small volume, and low surface tension. After coating, it can form a low surface energy surface, which has a small force on the adhesive, so it has good peeling performance. Therefore, a dense organic silicon polymer layer with a cross-linked network system structure formed on the surface of paper can prevent the adhesive from penetrating into the dense layer. Anti-sticking film with anti-sticking and isolation functions is mainly used in the production of self-adhesive label paper, pressure-sensitive adhesive paper, composite isolation paper for decorative materials, artificial leather release paper and isolation paper for medical diagnostic equipment, so that the treated substrate has anti-sticking and isolation properties.
[0003] Silicone release agents can be divided into three categories according to their physical form: solvent-based, emulsion-based and solvent-free. From the current development trend, solvent-based release agents have the advantages of easy preparation, convenient use, and low production environment requirements; but they also have disadvantages such as flammability, adverse health, and environmental pollution. Solvent-based condensation curing anti-adhesive agents have been generally restricted due to environmental pollution, harmful health and safety issues. The advantages of emulsion-based release agents are safe operation, no environmental pollution, and wide functions. Its disadvantages are high energy consumption for drying and easy wrinkling of paper. Due to the restrictions on the use of solvent-based release agents and the rapid development of film packaging materials, its development potential is still huge. The characteristics of solvent-free release agents are fast curing, energy saving, safety, and no pollution to the environment. At present, with the maturity of five-roll coating technology, low coating amount and uniform coating can be guaranteed under high-speed coating conditions, and solvent-free silicone release agents have been rapidly developed. According to the cross-linking reaction during the final coating, they can be divided into addition type, condensation type, and irradiation type. Compared with the degree of curing, peeling performance, anti-adhesion performance, and operability of coating formula design, the addition type is better than the condensation type. As my country's awareness of green economy increases, solvent-based silicone release agents have been gradually replaced.
[0004] From the patents reported so far, a material that imparts anti-sticking properties to viscous substances has been prepared. The material is mainly prepared by coating a curable siloxane composition on the surface of a sheet substrate such as paper, laminated paper, synthetic resin film and metal foil, and then thermally curing in the presence of a platinum catalyst to obtain a coating. The main components of the siloxane composition are organic polysiloxanes and organic hydrogen polysiloxanes with alkenyl groups. For example, Chinese patent application publication number CN1335344A discloses a siloxane composition, which contains low-viscosity organic polysiloxanes with hexenyl groups, polyorganohydrogen siloxanes and platinum catalysts. Among them, the organic hydrogen polysiloxane contains two types, one is a polyorganohydrogen siloxane with hydrogen at the end, and the other is a polyorganohydrogen siloxane with hydrogen at the side chain. The purpose of this patent is mainly to ensure that under the condition of high-speed coating (coating speed is greater than or equal to 500m / min), the composite can be quickly cured on the surface of paper or film, a stable release force can be obtained, and the cured film can be guaranteed to have good residual adhesion to viscous substances.
[0005] In actual production, before the release paper or release film is rolled up, a curing coating is coated with a sticky substance, and the curing coating will contact with metal or plastic foil or plastic roller, resulting in damage to the curing coating, which leads to poor sliding property of the curing coating and cannot be rolled up smoothly. Among them, JP61-159480A discloses a solvent-free addition reaction curing organopolysiloxane composition, in which, in addition to organopolysiloxane and organohydrogenpolysiloxane with alkenyl groups, a straight-chain organopolysiloxane with hydroxyl groups at the molecular end is also used as a basic component. Although it has been improved to a certain extent, satisfactory sliding property is still not obtained. In order to solve the problem of sliding property, Chinese patent application publication number CN101616995A proposes an organopolysiloxane composition, in which a main agent adopts an organosiloxane compound with multiple branching points, and the problem of sliding property is well solved by adopting the organosiloxane of this design. Chinese patent application publication number CN104817702A discloses a spherical dendritic organosilicon macromolecule and its preparation method and application. Active sites that can diverge are introduced into cyclic siloxane to prepare spherical dendritic macromolecules. However, it can only be used as an additive. The normal addition amount ranges from 1 to 2%. Excessive addition amount will also lead to the occurrence of self-crosslinking of the reactive active sites of the spherical dendritic organosilicon macromolecules.
[0006] Chinese patent application publication number CN103936999A discloses a silicon-containing compound, a curable composition and a cured product. The introduction of epoxy groups into cyclosiloxane can improve the curability of the curable composition and the heat resistance of the cured product. However, the introduction of epoxy groups will lead to an increase in the surface energy of the compound, thereby resulting in a decrease in the anti-sticking performance, which cannot meet the requirement of low surface energy of the release agent surface.
[0007] Chinese patent application publication number CN103481608B discloses a composite board and a preparation method thereof and a display substrate containing the same, wherein a crude product is prepared by reacting cyclic siloxane and linear terminal vinyl polysiloxane, which is then impregnated onto a substrate. Under heating conditions, the silicon hydrogen groups in the macromolecular polysiloxane in the crude product undergo a cross-linking reaction to cure into a silicone resin composite board; due to its low molecular branching degree, the reaction activity of silicon hydrogen on the macromolecule is low, and the reaction speed is slow, which cannot meet the requirements of applications requiring rapid curing.
[0008] The open journal Facile synthesis of cyclosiloxane-based polymers for hybrid film formation, [Polymer Chemistry] reported the preparation of intermediates by reacting cyclic siloxanes and small molecule linear terminal vinyl polysiloxanes. First, all the vinyl groups were reacted, and the remaining silicon hydrogen groups were used to produce a high molecular polymer through internal self-crosslinking reaction. Because the remaining silicon hydrogen groups easily react with water to produce easily condensed silanol groups, the product obtained needs to be stored in an inert gas and is prone to gelation in ordinary air environments, which cannot meet the needs of daily production.
[0009] The patents reported so far mainly focus on the solution of release force, sliding property and friction coefficient, as well as the residual adhesion rate problem that is generally concerned. However, the solvent-free polyorganosiloxane composition as an anti-adhesive generally has the problem of high aging release force. In this way, during use, the aging release force increases, which will cause the product to be difficult to tear apart during use, which will affect the performance of the product. This problem is mainly due to the fact that under high temperature and high speed conditions, some polymethylhydrogensiloxanes do not have time to react, and the reaction system is not completely cross-linked. In the subsequent storage process, the silicon hydrogen in the polymethylhydrogensiloxane undergoes cross-linking, and the silicon hydrogen in the polymethylhydrogensiloxane contacts a large amount of water vapor in the air, resulting in further hydrolysis and condensation reactions, which leads to an increase in cross-linking density. The increase in cross-linking density leads to an increase in aging release force.
[0010] At present, most of the literature uses the active groups between linear polysiloxanes to undergo cross-linking reactions. Under high temperature and high speed conditions, the probability of collision between the active groups between linear polysiloxanes is relatively small, which results in a large amount of silicon hydrogen in polymethylhydrogensiloxane not participating in the reaction. Summary of the invention
[0011] In order to overcome the deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide a branched organosilicon macromolecular polymer containing cyclic siloxane.
[0012] Another object of the present invention is to provide a method for preparing the branched organosilicon macromolecular polymer containing cyclic siloxane.
[0013] Another object of the present invention is to provide an application of the branched organosilicon macromolecular polymer containing cyclic siloxane.
[0014] The fourth object of the present invention is to provide a solvent-free polyorganosiloxane composite, which introduces a branched organosilicon macromolecular polymer containing cyclic siloxane to improve the reactivity and curing speed of the reactive functional groups of the system, form a fully cured anti-stick coating, obtain a stable release force, reduce the amount of polyorganohydrogensiloxane used, and reduce the increase in aging release force under room temperature storage conditions.
[0015] The purpose of the present invention is achieved through the following technical solutions:
[0016] An organosilicon polymer, the structural formula of which is shown as Formula I, wherein the structural formula of N is shown as Formula II,
[0017]
[0018] The R1 is an alkyl group; preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group or a decyl group, and more preferably a methyl group;
[0019] The R2 is an alkyl group or a reactive alkenyl group; preferably an alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, or a reactive alkenyl group such as vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl, more preferably a methyl group or vinyl group;
[0020] The R3 is an alkyl group, an aryl group or an aralkyl group; preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, a phenyl group, a tolyl group, a xylyl group, a benzyl group, a phenethyl group, etc.;
[0021] The R4 is an alkyl group or a reactive alkenyl group; preferably, an alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, or a reactive alkenyl group such as vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl, more preferably, a methyl group or a vinyl group;
[0022] m and n are the numbers of links of the repeating units in the molecule; m is preferably 1-1,000,000, more preferably 1-10,000; n is preferably 1-1,000,000, more preferably 1-10,000.
[0023] The method for preparing the organosilicon polymer of the present invention comprises the following steps:
[0024] (1) tetravinylsilane is added dropwise to tetramethyltetrahydrocyclotetrasiloxane, and a crude product of an organosilicon polymer is obtained by a hydrosilylation reaction under the action of a catalyst and certain conditions, and low volatiles are removed under reduced pressure to obtain an organosilicon intermediate of formula III;
[0025]
[0026]
[0027] (2) adding the organosilicon intermediate of formula III dropwise to the vinyl-terminated polyorganosiloxane, and obtaining a crude product of the organosilicon polymer through a hydrosilylation reaction under the action of a catalyst and certain conditions, and removing low volatiles under reduced pressure to obtain the organosilicon polymer.
[0028]
[0029] In the vinyl-terminated polyorganosiloxane, R1 is methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl or decyl, and more preferably methyl;
[0030] R2 is an alkyl group, such as a chain alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, or a reactive chain alkenyl group such as vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl, more preferably a methyl or vinyl group;
[0031] R3 is an alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl or decyl, an aryl group such as phenyl, tolyl or xylyl, or an aralkyl group such as benzyl or phenethyl;
[0032] R4 is an alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, or a reactive alkenyl group such as vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl, more preferably methyl or vinyl;
[0033] m and n are the number of links of the repeating units in the molecule; m is preferably 1-1,000,000, more preferably 1-10,000; n is preferably 1-1,000,000, more preferably 1-10,000. The viscosity of the corresponding polymer is preferably 1-5,000,000 cP, more preferably 1-500,000 cP.
[0034] The catalyst of the present invention is preferably at least one of chloroplatinic acid, chloroauric acid, a Custer catalyst and a platinum-carbon catalyst, preferably a Custer catalyst.
[0035] In step (1) and step (2) of the present invention, the reaction conditions of the hydrosilylation reaction are: stirring the reaction at 5-50°C for 2-48h, preferably stirring the reaction at 1-30°C for 4-24h.
[0036] A solvent-free polyorganosiloxane composite, comprising the following components: a mixture of the organosilicon polymer of the present invention, polymethyl hydrogen siloxane, a catalyst G and an inhibitor;
[0037] The composite is preferably composed of 80-98 parts of organosilicon polymer, 1-10 parts of polymethyl hydrogen siloxane, 0.5-10 parts of catalyst G, and 0.01-1 parts of inhibitor per 100 parts of the composite in terms of mass ratio.
[0038] The catalyst G described in the present invention is a Group VIII catalyst for rapidly forming a cross-linked film under high temperature conditions, preferably an organic active platinum complex or a rhodium complex; more preferably an organic active platinum complex, the composition of which is a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum.
[0039] The inhibitor described in the present invention is an inhibitor that can prevent gelation and solidification within a specified temperature range to maximize the life of the bath and quickly crosslink and solidify under high temperature and high speed conditions; the specified temperature range is 5 to 60°C, the bath life is 6 to 24 hours, the high temperature range is 100 to 230°C, and the high speed range is 50 to 1500 m / min.
[0040] The inhibitor of the present invention is preferably at least one of alkynol compounds, ene yne compounds, organic nitrogen compounds, organic phosphorus compounds and acid anhydride compounds, and is further preferably alkynol compounds and acid anhydride compounds. The alkynol compound is preferably 3-methyl-1-butynol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-hexyn-3-ene or 1-ethynyl-1-cyclohexanol; the acid anhydride compound is preferably dimethyl maleate or dimethyl fumarate.
[0041] The solvent-free polyorganosiloxane composite of the present invention is coated on various substrates such as paper, polyolefin-laminated paper, synthetic resin film, coated paper and metal foil, and then cured at high temperature to form a release coating that can be peeled off from sticky substances on the substrate surface.
[0042] Compared with the prior art, the present invention has the following advantages and effects:
[0043] (1) The introduction of branched organosilicon macromolecular polymers containing cyclic siloxanes makes the solvent-free polyorganosiloxane composite more reactive, and under rapid coating conditions, the cross-linked network structure formed is more perfect, thereby obtaining a polyorganosilicon anti-stick coating with more stable release force;
[0044] (2) The introduction of branched organosilicon macromolecular polymers containing cyclic siloxanes allows the Si-H in the polymethylhydrogensiloxane in the solvent-free polyorganosiloxane composite to react completely under rapid coating conditions, thereby ensuring the stability of the aged release force under room temperature storage conditions;
[0045] (3) The introduction of branched organosilicon macromolecular polymers containing cyclic siloxanes can reduce the amount of polymethylhydrogensiloxane in the solvent-free polyorganosiloxane to a certain extent, thereby fundamentally reducing the possibility of an increase in release force under room temperature storage conditions;
[0046] (4) The introduction of branched organosilicon macromolecular polymers containing cyclic siloxanes can, to a certain extent, improve the residual adhesion rate of the solvent-free polyorganosiloxane composite when cured onto a sheet-like substrate, thereby ensuring that the polyorganosiloxane will not migrate during subsequent use.
[0047] (5) The introduction of branched silicone macromolecular polymers containing cyclic siloxanes can reduce the amount of catalyst used to a certain extent without affecting the release performance, thereby reducing production costs. DETAILED DESCRIPTION
[0048] The principles and features of the present invention are described below. The examples used are only used to explain the present invention and are not used to limit the scope of the present invention.
[0049] The test was conducted using standard test tapes Tesa7475 and Nitto 31B, and the three indicators of release force, aging release force, and residual adhesion were used as performance indicators to evaluate the product. The test method is briefly described as follows:
[0050] Determination of release force: Use a force sensor type peeling force tester, with a stretching speed of 30cm / min, a stretching distance of 100mm, and a sample size of 150×25mm. Test method: Paste the commercially available pressure-sensitive Tesa7475 tape to the surface of the offset paper coated with a release agent (cured film), taking care not to create an air gap inside (roll back and forth twice with a 2kg pressure roller), and then perform a 180° peeling test.
[0051] Determination of aging release force: Use a force sensor type peeling force tester, with a tensile speed of 30cm / min, a tensile distance of 100mm, and a sample size of 1500×25mm. Test method: Paste the commercially available pressure-sensitive Tesa7475 tape to the surface of the offset paper coated with a release agent (cured film), and pay attention to not creating air gaps inside (roll back and forth twice with a 2kg roller), then age at 70℃ for 20h, and then perform a 180° peel test.
[0052] Determination of residual adhesion rate: Residual adhesion is to measure the decrease in adhesion caused by silicone migration. Paste the commercial Nitto 31B tape to the surface of offset paper coated with release agent (cured film), and pay attention not to generate air gaps inside (roll back and forth twice with a 2kg roller), then age it at 70°C for 20h, then peel off the Nitto 31B tape, transfer it to PET, roll back and forth twice with a 2kg pressure, and perform a 180° peeling test after 1h. The force measured is F1. At the same time, paste the Nitto 31B tape on PET, roll back and forth twice with a 2kg pressure, and perform a 180° peeling test after 1h. The force measured is F2. The value obtained by F1 / F2*100% is the residual adhesion rate.
[0053] Example 1
[0054] 96.2 g of tetramethyltetrahydrocyclotetrasiloxane was added to a flask, stirring was started, and the mixture was heated to 20° C. at 100 RPM. 0.5 g of Karstedt catalyst (wherein the content of platinum metal was 5000 ppm, and the structure of Karstedt catalyst was a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum) was added. 13.6 g of tetravinylsilane was added dropwise at a dropping rate of 5 ml / min. The mixture was stirred at this temperature for 20 h, and then heated to 110° C., vacuumed, and low-boiling substances were removed to obtain an organosilicon intermediate (Formula III).
[0055] Silicone intermediates 1 H NMR, where δ 0.7 ppm is the chemical shift of hydrogen at position 1, δ 1.06 ppm is the chemical shift of hydrogen at position 2, δ 0.14 ppm is the chemical shift of hydrogen at position 3, δ 4.7 ppm is the chemical shift of hydrogen at position 4, and δ 0.19 ppm is the chemical shift of hydrogen at position 5.
[0056]
[0057] Example 2
[0058] Add 800g of vinyl-terminated polydimethylsiloxane (viscosity 200CP, brand: SY-200) into a flask, start stirring, 100RPM, heat to 20°C, add 4.5g of Karstedt catalyst (wherein the content of platinum metal is 5000ppm, and the structure of Karstedt catalyst is a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum), add 95.1g of organosilicon intermediate (prepared in Example 1) dropwise at a dropping rate of 5ml / min, keep warm and stir for 20h, then heat to 110°C, evacuate, remove low-boiling substances, and obtain an organosilicon polymer (Formula II-1), wherein the structural formula of group R is as shown in Formula II-2.
[0059] Silicone polymer 1 H NMR, where δ 1.06 ppm is the chemical shift of hydrogen at positions 1, 2, and 11, δ 0.21 ppm is the chemical shift of hydrogen at position 3, δ 0.14 ppm is the chemical shift of hydrogen at positions 4, 5, 8, and 9, δ 5.17-5.3 ppm is the chemical shift of hydrogen at positions 6 and 7, and δ 0.7 ppm is the chemical shift of hydrogen at position 10.
[0060]
[0061] Example 3
[0062] 100 g of an organosilicon polymer (prepared in Example 2), 1 g of polymethylhydrogensiloxane (polymethylhydrogensiloxane with trimethylsiloxane end-capping at both ends of the molecule, viscosity of 20 mPa.s, brand: 1107), and 0.2 g of 1-ethynyl-1-cyclohexanol were mixed uniformly, and then 2 g of a Karstedt catalyst (wherein the content of platinum metal was 5000 ppm, and the structure of the Karstedt catalyst was a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum) was added to the mixture to form a solvent-free polyorganosiloxane composite S1, and then the composite S1 was coated on glassine paper by a coating machine at a coating speed of 500 m / min, a drying oven temperature of 200° C., and a drying oven length of 32 m to obtain a release paper product with a silicon coating amount of 1.012 g / m 2 The release force of the release paper tested was 8.1 g / inch, the aged release force was 13.6 g / inch, and the residual adhesion rate was 96.6%.
[0063] Example 4
[0064] 100 g of an organosilicon polymer (prepared in Example 2), 1 g of polymethylhydrogensiloxane (polymethylhydrogensiloxane with trimethylsiloxane end-capping at both ends of the molecule and a viscosity of 20 mPa.s), and 0.2 g of 1-ethynyl-1-cyclohexanol were mixed uniformly, and then 1.5 g of a Karstedt catalyst (wherein the content of platinum metal was 5000 ppm, and the structure of the Karstedt catalyst was a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum) was added to the mixture to form a solvent-free polyorganosiloxane composite S2, and then the composite S2 was coated on glassine paper by a coating machine at a coating speed of 500 m / min, a drying oven temperature of 200° C., and a drying oven length of 32 m to obtain a release paper product with a silicon coating amount of 1.023 g / m 2 The release force of the release paper tested was 8.5 g / inch, the aged release force was 14.2 g / inch, and the residual adhesion rate was 95.2%.
[0065] Comparative Example 1
[0066] 100 g of vinyl-terminated polydimethylsiloxane (viscosity 200 cp), 2.06 g of polymethylhydrogensiloxane (polymethylhydrogensiloxane with trimethylsiloxane end-capping at both ends of the molecule and a viscosity of 20 mPa.s), and 0.2 g of 1-ethynyl-1-cyclohexanol were mixed uniformly, and then 2 g of Karstedt catalyst (wherein the content of platinum metal was 5000 ppm, and the structure of the Karstedt catalyst was a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum) was added to the mixture to form a solvent-free polyorganosiloxane composite S3, and then the composite S3 was coated on glassine paper by a coating machine at a coating speed of 500 m / min, a drying oven temperature of 200° C., and a drying oven length of 32 m to obtain a release paper product with a silicon coating amount of 1.018 g / m 2 The release force of the release paper tested was 12.5 g / inch, the aged release force was 20.6 g / inch, and the residual adhesion rate was 82.3%.
[0067] Comparative Example 2
[0068] 100 g of vinyl-terminated polydimethylsiloxane (viscosity 200 cp), 2.06 g of polymethylhydrogensiloxane (polymethylhydrogensiloxane with trimethylsiloxane end-capping at both ends of the molecule and a viscosity of 20 mPa.s), and 0.2 g of 1-ethynyl-1-cyclohexanol were mixed uniformly, and then 1.5 g of Karstedt catalyst (wherein the content of platinum metal was 5000 ppm, and the structure of the Karstedt catalyst was a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum) was added to the mixture to form a solvent-free polyorganosiloxane composite S3, and then the composite S3 was coated on glassine paper by a coating machine at a coating speed of 500 m / min, a drying oven temperature of 200° C., and a drying oven length of 32 m to obtain a release paper product with a silicon coating amount of 1.022 g / m 2 The release force of the release paper tested was 15.7 g / inch, the aged release force was 29.3 g / inch, and the residual adhesion rate was 75.1%.
Claims
1. An organosilicon polymer, the structural formula of which is shown as Formula I, wherein: The structural formula of N is shown as Formula II, Among them, R1 is an alkyl group; R2 is an alkyl group or a reactive alkenyl group; R3 is an alkyl group, an aryl group or an aralkyl group; R4 is an alkyl group or a reactive alkenyl group; m and n are the number of links of the repeating units in the molecule; m is 1-1000000; and n is 1-1000000.
2. The organosilicon polymer according to claim 1, characterized in that R1 is methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl or decyl; R2 is methyl, ethyl, propyl, butyl, pentyl or hexyl, or vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl; R3 is methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, phenyl, tolyl, xylyl, benzyl, or phenethyl; R4 is methyl, ethyl, propyl, butyl, pentyl, hexyl, or vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl; m is 1-10000; n is 1-10000.
3. A method for preparing the organosilicon polymer according to claim 1, comprising the following steps: (1) tetravinylsilane is added dropwise to tetramethyltetrahydrocyclotetrasiloxane, and a crude product of an organosilicon polymer is obtained by a hydrosilylation reaction under the action of a catalyst and certain conditions, and low volatiles are removed under reduced pressure to obtain an organosilicon intermediate of formula III; (2) adding the organosilicon intermediate of formula III dropwise to the vinyl-terminated polyorganosiloxane, obtaining a crude organosilicon polymer product through a hydrosilylation reaction under the action of a catalyst and certain conditions, and removing low volatiles under reduced pressure to obtain an organosilicon polymer; The structural formula of the vinyl-terminated polyorganosiloxane is: in, R1 is an alkyl group; R2 is an alkyl group or a reactive alkenyl group; R3 is an alkyl group, an aryl group or an aralkyl group; R4 is an alkyl group or a reactive alkenyl group; m and n are the number of links of repeating units in the molecule; m is 1-1000000; and n is 1-1000000.
4. The method according to claim 3, characterized in that: R1 is methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl or decyl; R2 is methyl, ethyl, propyl, butyl, pentyl or hexyl, or vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl; R3 is methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, phenyl, tolyl, xylyl, benzyl, or phenethyl; R4 is methyl, ethyl, propyl, butyl, pentyl, hexyl, or vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl or decenyl; m is 1-10000; n is 1-10000.
5. The method according to claim 3, characterized in that: The catalyst is at least one of chloroplatinic acid, chloroauric acid, Custer catalyst and platinum-carbon catalyst.
6. The method according to claim 3, characterized in that In step (1) and step (2), the reaction conditions of the hydrosilylation reaction are: stirring the reaction at 5 to 50° C. for 2 to 48 hours.
7. The method according to claim 3, characterized in that In step (1) and step (2), the reaction conditions of the hydrosilylation reaction are: stirring the reaction at 1-30° C. for 4 to 24 hours.
8. A solvent-free polyorganosiloxane composite, comprising the following composition: a mixture of the organosilicon polymer according to claim 1 or 2, polymethylhydrogensiloxane, a catalyst G and an inhibitor.
9. The composite according to claim 8, characterized in that The composite comprises, by mass ratio, 80-98 parts of the organosilicon polymer, 1-10 parts of the polymethyl hydrogen siloxane, 0.5-10 parts of the catalyst G and 0.01-1 parts of the inhibitor in every 100 parts of the composite.
10. The composite according to claim 8, characterized in that The catalyst G is an organic active platinum complex or rhodium complex.
11. The composite according to claim 8, characterized in that The catalyst G is a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and platinum.
12. The composite according to claim 8, characterized in that The inhibitor is at least one of alkynol compounds, ene-yne compounds, organic nitrogen compounds, organic phosphorus compounds and acid anhydride compounds.
13. The composite according to claim 12, characterized in that The inhibitor is one or more of 3-methyl-1-butyn-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-hexyn-3-ene or 1-ethynyl-1-cyclohexanol, dimethyl maleate and dimethyl fumarate.
Citation Information
Patent Citations
Solventless cured release coating-forming organopolysiloxane composition and sheet-form substrate having cured release coating
CN101616995A
Composite board, its preparation method and display substrate comprising it
CN103481608B
Silicon-containing compound, curable composition and cured product
CN103936999A
Siloxane composition using for forming anti-adhesive coating
CN1335344A
Silicone composition for release paper
JP1986159480A